The decline of neo-liberalism and the rise of neo-keynesianism: a conceptual analysis - Permadi, Dedy (Ciência & Trópico, 2013)
ABSTRACT Liberal thoughts have always experienced dynamic movements by giving birth to varieties of thoughts within the liberal thought itself. This is expressed on the development of this thought from the idea of classical liberalism, Keynesian political economy, and also Hayek’s ideas which remains the dominant idea until this current time. However, in the development of the contemporary global political economy, the neo-liberal thought has started to receive a strong criticism. This article thesis focus on analytical ideas that will then be the tools to analyze the opportunity of the spread of the neo-Keynesianism idea in the dominancy of Hayek’s Ideas. In the contemporary era, the Keynesianism idea is being brought back to the surface in order to answer various global challenges which are difficult to be solved through neo-liberal schemes. This idea is considered “easy” bearing in mind how the world is currently at a massive economic crisis which requires the people to have alternative ideas in order to solve their problems. This development depends also on the part of the actors/agents who represent those who are pro-Keynesianism, such as Joseph Stiglitz and Paul Krugman. This effort will keep on being continued up to a point where the neo-Keynesianism ideas gain the political support and legitimacy to be implemented in the practical fields. This opportunity still requires a long process due to various factors such the limited supporting political power and the people’s acceptance which can still be considered very weak. KEYWORDS: Neo-keynesianism. Development. Political power. O declínio do neoliberalismo e a ascensão do neo-keinesianismo: uma análise conceitual RESUMO Pensamentos liberais têm experimentado sempre os movimentos dinâmicos, dando origem a variedades de pensamentos dentro do próprio pensamento liberal. Isso está expresso no desenvolvimento deste pensamento a partir da ideia do liberalismo clássico, em que tanto na economia política keynesiana, como também nas ideias de Hayek, permanece o pensamento dominante até o momento atual. No entanto, no desenvolvimento da economia política contemporânea global, o pensamento neo-liberal começou a receber uma forte crítica. O foco desta tese é sobre ideias analíticas que serão, então, as ferramentas para analisar a oportunidade da difusão da ideia do neo-keynesianismo na dominância de ideias de Hayek. Na era contemporânea, o pensamento keynesiano está sendo trazido de volta à superfície, a fim de responder a diversos desafios globais que são difíceis de serem resolvidos por meio de esquemas neo-liberais. Esta ideia é considerada “fácil”, tendo em mente como o mundo está atualmente em uma enorme crise econômica que exige que as pessoas tenham ideias alternativas, a fim de resolver seus próprios problemas. Esse desenvolvimento depende também da parte dos atores/agentes que representam aqueles que são pró-keynesianismo, como Joseph Stiglitz e Paul Krugman. Esse esforço vai ser continuado até um ponto em que as ideias neo-keynesianistas ganharem o apoio político e a legitimidade para serem implementadas nos campos práticos. Essa oportunidade ainda requer um longo processo devido a vários fatores, tais como o limitado e sustentado poder político e a aceitação das pessoas, o que ainda pode ser considerada muito fraca. PALAVRAS-CHAVE: Neo-keynesianismo. Desenvolvimento. Poder político.